The least value of the expression 2 l o g 1 0 x − l o g x ( 0 . 0 1 ) for x > 1 is :-
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The idea is quite good, but you also have to reason why equality holds in the AM-GM inequality for some value of x .
( a − 1 ) 2 ≥ 0 , ∀ a ∈ R +
⟹ a 2 − 2 a + 1 ≥ 0 ⟹ a 2 + 1 ≥ 2 a
⟹ a + a 1 ≥ 2 positive real numbers property
E ( x ) = 2 ⋅ l o g 1 0 x − l o g x 0 . 0 1 = 2 ⋅ ( l o g 1 0 x + l o g x 1 0 )
y = l o g x 1 0 → x y = 1 0 → ( x y ) y 1 = 1 0 y 1 → x = 1 0 y 1 → l o g 1 0 x = y 1
Substituting, comes:
E ( x ) = 2 ⋅ [ y ( x ) 1 + y ( x ) ]
Hence, verified existential conditions, minimum is:
m i n [ E ( x ) ] = 2 ⋅ 2 = 4
Problem Loading...
Note Loading...
Set Loading...
We see that 2 l o g 1 0 x − l o g x ( 1 0 ) ( − 2 ) = 2 l o g 1 0 x + 2 l o g x 1 0 = 2 l o g 1 0 x + 2 l o g 1 0 1 x = 2 ( l o g 1 0 x + l o g 1 0 x 1 ) Using A M ≥ G M ,we get :- 2 l o g 1 0 x + l o g 1 0 x 1 ≥ ( l o g 1 0 x . l o g 1 0 x 1 ) 1 / 2 ⟹ l o g 1 0 x + l o g 1 0 x 1 ≥ 2 or 2 l o g 1 0 x − l o g x ( 0 . 0 1 ) ≥ 4 So ,least value is 4 . ⌣ ¨